The male imago of Rivudiva trichobasis Lugo-Ortiz & McCafferty from Amazonas state, Brazil - Cruz, Paulo Vilela; Boldrini, Rafael; Salles, Frederico Falcão; Hamada, Neusa (Zootaxa, 2011)
The genus Rivudiva Lugo-Ortiz and McCafferty (Ephemeroptera: Baetidae) was established to include two species: Rivudiva minantenna Lugo-Ortiz and McCafferty described from Southern Brazil and Rivudiva trichobasis Lugo-Ortiz and McCafferty described from Southern Brazil and Paraguay. Later, Salles & Nascimento (2009) described the imagos of R. minantenna and transferred Camelobaetidius coveloae (Traver), originally placed in Baetis Leach and Cloeodes venezuelensis (Traver) originally placed in Pseudocloeon Klapálek to Rivudiva.